Предмет: Математика,
автор: temchenkodima2009
Доведіть тотожність 2( n + р) - 4 m = 2( -n + m) - 6( m - p) + 4(n - p) різними способами.
Ответы
Автор ответа:
1
Пошаговое объяснение:
2(n + p) - 4m = 2(-n + m) - 6(m - p) + 4(n - p)
2n + 2p - 4m = -2n + 2m - 6m + 6p + 4n - 4p
2n + 2p - 4m = 2n + 2p - 4m
Похожие вопросы
Предмет: Информатика,
автор: Sasha070208
Предмет: Математика,
автор: robert123standoff2
Предмет: Математика,
автор: annakorol32
Предмет: Литература,
автор: polinabaluevaA
Предмет: Қазақ тiлi,
автор: Аноним